The effect of discipline and work culture on employees performance at PT. XYZ - Widiyanto; Budi Rismayadi; Neni Sumarni (Institute of Computer Science (IOCS), 2023)
Attitudes and habits at work really need to be considered, especially the discipline and work culture of an employee in order to avoid disciplinary actions that will affect the performance of individual employees, groups or the company itself. This study aims to examine the significant influence of discipline and work culture on employee performance in the quality control department at PT XYZ either partially or simultaneously. the number of population taken is 69 people to make the population a sample by using non-probability sampling technique in saturated sampling. Observations and questionnaires were used as data collection in this study, while SPSS V.26 software was used for data analysis. The data analysis technique was carried out using multiple linear regression analysis methods. Based on the analysis carried out 1) there is a positive and significant effect partially between discipline variables on employee performance. 2) there is a positive and significant effect partially between variables on employee performance. 3) there is a positive and significant simultaneous influence between the variables of discipline and work culture on employee performance.